A Subcentimetric Nodule on the Penile Shaft. (September 2020) - Majumder, Rishila; Biswas, Dipanwita; Mishra, Tushar Subhadarshan; Mitra, Suvradeep
Juvenile xanthogranuloma (JXG) is a benign histiocytic disorder usually affecting the head and trunk region of a child. The isolated occurrence of JXG in the penile shaft of a young adult is hitherto unreported. This lesion is amenable to surgical resection although systemic and/or internal visceral involvement can occur. The clinical differential of this solid cystic lesion may include other solid cystic lesions of the penile shaft, namely, epidermal inclusion cyst. A typical yellowish color can aid in the diagnosis though it is not a constant feature. In this article, we discuss a case of isolated penile JXG in a young adult with salient clinical and histopathological differentials.